The effectiveness of published continuum constitutive laws to predict stress-assisted densification of powder compacts - Camacho Montes, Hector (2022)
Commonly used constitutive laws for crystalline and viscous materials have been compared to predict the densification behavior under hot-pressing and sinter-forging. Experimental results, from literature for one loading condition, have been used to extract the constitutive laws for amorphous and crystalline materials and, these in-turn, have been used to predict behavior under a different set of loading conditions. Ideally, the constitutive parameters obtained from one set of loading conditions and thermal history should apply to a different set of conditions. However, there is a lack of systematic experimental studies in which this can be checked. In this paper, we use constitutive parameters obtained from one set of conditions to predict the densification response under a different set of loading conditions. For both sintering of amorphous and crystalline materials, we use two different constitutive parameters and compare the predictions of these for the case where experimental results are not available. In addition, the effect of temperature on densification behavior for stress-assisted sintering has been investigated. It is shown that the two commonly used constitutive models for viscous sintering (Scherer and Skorohod–Olevsky) predict similar behavior for amorphous materials. However, for crystalline materials, the predictions of the Riedel–Svoboda and the Kuhn–Sofronis–McMeeking (KSM) models are different. Finally, it is shown that the dependence of the normalized densification on temperature, under constant heating rate conditions, with parameters obtained from isothermal experiments, is a good test for the models.